2014
DOI: 10.1007/s11032-014-0034-2
|View full text |Cite
|
Sign up to set email alerts
|

Allele frequencies in the VRN-A1, VRN-B1 and VRN-D1 vernalization response and PPD-B1 and PPD-D1 photoperiod sensitivity genes, and their effects on heading in a diverse set of wheat cultivars (Triticum aestivum L.)

Abstract: Heading of cereals is determined by complex genetic and environmental factors in which genes responsible for vernalization and photoperiod sensitivity play a decisive role. Our aim was to use diagnostic molecular markers to determine the main allele types in VRN-A1, VRN-B1, VRN-D1, PPD-B1 and PPD-D1 in a worldwide wheat collection of 683 genotypes and to investigate the effect of these alleles on heading in the field. The dominant VRN-A1, VRN-B1 and VRN-D1 alleles were present at a low frequency. The PPD-D1a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
64
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(74 citation statements)
references
References 51 publications
(109 reference statements)
8
64
0
2
Order By: Relevance
“…A recent study carried out on ~700 T. aestivum cultivars from different geographical origins reported that only 7% of the samples analysed carried spring alleles in VRN‐A1 (Kiss et al. ). Our analysis of 30 durum wheat accessions with specific molecular markers demonstrated a clear preponderance of spring dominant alleles at the VRN‐A1 locus (93% of accessions).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study carried out on ~700 T. aestivum cultivars from different geographical origins reported that only 7% of the samples analysed carried spring alleles in VRN‐A1 (Kiss et al. ). Our analysis of 30 durum wheat accessions with specific molecular markers demonstrated a clear preponderance of spring dominant alleles at the VRN‐A1 locus (93% of accessions).…”
Section: Discussionmentioning
confidence: 99%
“…The major allele types of the 19 wheat cultivars in the VRN and the PPD genes (Table 1) were determined using gene allele specific primers as listed in Kiss et al (2014). In addition, they were subjected to the 15K Illumina SNP platform (TraitGenetics Ltd, Gatersleben, Germany), which resulted in 4971 polymorphic markers after leaving out those with any missing values, being monomorphic, or rare alleles (characteristic to only one genotype) or showing complete linkage within the same genetic distance in the consensus marker map provided by the company.…”
Section: Genotypic Characterizationmentioning
confidence: 99%
“…In wheat, the photoperiod insensitivity alleles in the PPD1 genes result in rapid heading irrespective of the photoperiod. While the role of PPD‐A1 is not significant in Triticum aestivum , several functional polymorphisms were identified in PPD‐B1 and PPD‐D1 leading to significant variations in heading date (Beales et al ; Diaz et al 2012; Kiss et al ). The basis of insensitivity is the increased gene copy number in the PPD‐B1 locus, while in the case of PPD‐D1 gene, it is a large deletion of 2089 bp in the promoter region leading to overexpression (Beales et al .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a diverse set of predominantly winter wheat cultivars from Europe was screened for vernalization and photoperiod alleles (Kiss et al. ). European wheat cultivars with spring type of growth have not been studied systematically in this regard.…”
mentioning
confidence: 99%